Prevention and control of catheter-associated urinary tract infections - implementation of the recommendations of the Commission for Hospital Hygiene and Infection Prevention (KRINKO) in nursing homes for the elderly in Frankfurt am Main, Germany - Heudorf, Ursel; Gasteyer, Stefanie; Müller, Maria; Samoiski, Yvonne; Serra, Nicole; Westphal, Tim (German Medical Science GMS Publishing House, 2016)
Introduction: Urinary tract infections range among the most frequent infections not only in hospital patients but also in residents of long-term care facilities for the elderly. Urinary catheters are the greatest risk factor for urinary tract infections. In the guidance paper on the "prevention of infections in nursing homes" (2005) as well as in the updated recommendations for the "prevention and control of catheter-associated urinary tract infections" (2015), the Commission for Hospital Hygiene and Infection Prevention (KRINKO) has recommended adequate preventive measures. In 2015, the implementation of these KRINKO recommendations was investigated.Method: All of Frankfurt's 40 nursing homes were evaluated using a checklist based on the KRINKO recommendations. The evaluation included assessing the availability of operating instructions, appropriate indications for the placement of catheters etc. Age, sex and duration of catheterization, as well as current and previous infections within the past 6 months were documented for every resident with a catheter.Results: In 35 (87.5%) of the nursing homes, operating instructions for the handling of urinary tract catheters were available. The decision as to whether a catheter is indicated is made by physicians, while its placement is often delegated to the nursing service. Typically, silicon catheters are used. In three-quarters of the nursing homes, regular intervals of 4-6 weeks for changing catheters were reported. On the respective survey day, 7.3% of the residents were catheterized. On the survey day, 3.6% (4.2%) and in the previous 6 months a total of 28% (28.9%) of the residents had a urinary tract infection (prevalence of antibiotic therapy in parentheses). Ciprofloxacin was used most often followed by cefuroxime and cotrimoxazole.Discussion: In the current evaluation, fewer nursing home residents were catheterized than in previous years and the rate of urinary tract infections was low. This indicates an increasingly cautious and apparently appropriate usage of urinary tract catheters. Also, the prevalence of antibiotic therapy was low for residents with urinary tract catheters (4.2%). However, broad spectrum antibiotics are still preferentially administered (particularly quinolones), which may favor the high rate of colonization with ESBL-producing bacteria and 3MRGN. Given this background, a coordinated approach including resistance-based antibiotic stewardship appears increasingly important in nursing homes and other health care facilities.